Trastornos hipertensivos y su relación con complicaciones materno – fetales en gestantes adolescentes atendidas en el Hospital Sagrado Corazón de Jesús, Quevedo, octubre 2024 – mayo 2025. - Alarcón Farinango, Alison Michelle (2025)
This research focuses on hypertensive disorders during pregnancy and their connection to maternal and fetal complications in pregnant adolescents who received care at the Sagrado Corazón de Jesús Hospital in Quevedo, Ecuador, from October 2024 to May 2025. Conditions like gestational hypertension and preeclampsia remain among the leading causes of health complications for both mothers and their babies, particularly in teenage pregnancies. The main goal is to explore how these disorders impact adolescent pregnancies, by determining their prevalence, identifying associated risk factors, and evaluating the quality of medical care provided. This is an applied, field-based, descriptive, and cross-sectional study that incorporates inductive, deductive, and historical-analytical methods. Data collection will be based on structured surveys and the review of clinical records. The findings aim to support improvements in healthcare services and help prevent complications in adolescent mothers.